PENGARUH STRUKTUR KEPEMILIKAN DAN GROWTH OPPORTUNITY TERHADAP STRUKTUR MODAL: For Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) 2015-2020 - Netta Algina Yudhianie; Ade Imam Muslim (Universitas Katolik Indonesia Atma Jaya, 2023)
The purpose of this study was to determine the effect of ownership structure and growth opportunities on the capital structure of manufacturing companies listed on the Indonesia Stock Exchanged (IDX) in 2015-2020. The ownership structure used is managerial ownership, institusional ownership, foreign ownership, independent commissioner, and audit committee. Meanwhile, growth opportunity is measured using GROWTH, namely the total asset of the current period minus the total asset of the previous period and divided by the total assets of the previous period. This research was conducted using quantitative methods with a descriptive and verificative approach, while the population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020. The number of samples used is 13 companies that are members of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2020, using a purposive sampling technique. The result of research conducted with a significant level of 5% indicated that the ownership structure and growth opportunity variables simultaneously significant effect on capital structure by 93.7% and the remaining 6.3% is influenced by other factors. Partially managerial ownership, institusional ownership, audit committee, and growth opportunity have a significant and significant effect on capital structure, while foreign ownership and independent commissioners has no significant effect on capital structure.